Characterisation and Properties of Al/ZnO Composites as Catalyst for Depolymerisation of Low Density Polyethylene to Liquid Oil - Nurul Razliana Abdul Razak (School of Materials Engineering, 2012)
This research study focussed on the investigation of physical, mechanical and microstructure of the Al/ZnO and Al/MTS composites with and without the presence of a binder.